2021
DOI: 10.3390/jcm10091869
|View full text |Cite
|
Sign up to set email alerts
|

Low Hypoperfusion Intensity Ratio Is Associated with a Favorable Outcome Even in Large Ischemic Core and Delayed Recanalization Time

Abstract: In ischemic brain tissue, hypoperfusion severity can be assessed using the hypoperfusion intensity ratio (HIR). We evaluated the link between HIR and clinical outcomes after successful recanalization by endovascular treatment. We retrospectively reviewed 162 consecutive patients who underwent endovascular treatment for intracranial large vessel occlusion. The HIR was calculated using an automated software program, with initial computed tomography perfusion images. The HIR was compared between patients with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…Analogously, we found that ASPECTS at baseline and on follow-up imaging and the risk of developing malignant edema were significantly associated with the HIR. The median HIR in our study lies within the range of the cutoff values applied in previous studies (0.4–0.7) [ 17 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, further research is necessary to define a generally valid cutoff value for HIR.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Analogously, we found that ASPECTS at baseline and on follow-up imaging and the risk of developing malignant edema were significantly associated with the HIR. The median HIR in our study lies within the range of the cutoff values applied in previous studies (0.4–0.7) [ 17 , 18 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, further research is necessary to define a generally valid cutoff value for HIR.…”
Section: Discussionsupporting
confidence: 83%
“…Both over- and underestimation of the FIV may have important consequences in the management of acute stroke, especially in cases where the decision whether to perform MT or not is not obvious. Such delicate cases particularly apply to patients with very advanced age or in whom secondary referral to a thrombectomy center involves delays for transportation [ 21 , 24 , 25 , 26 ]. HIR might be helpful in assessing the situation and making rational decisions in this time-sensitive phase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the ischemic core volume itself, the mismatch between the core and the tissue at risk (commonly called penumbra) plays a pivotal role in patient selection for MT [ 4 , 7 ]. Hypoperfusion intensity ratio (HIR) is used to assess collateral status with low HIR being associated with robust collaterals and described as a potential selection factor for thrombectomy eligibility and a predictor of favorable outcome [ 8 , 9 ]. Despite residual uncertainties regarding the benefit of MT beyond 6 h from symptom onset in large ischemic cores, the short-term benefit of MT in this population after selection by advanced imaging criteria are well known [ 9 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoperfusion intensity ratio (HIR) is used to assess collateral status with low HIR being associated with robust collaterals and described as a potential selection factor for thrombectomy eligibility and a predictor of favorable outcome [ 8 , 9 ]. Despite residual uncertainties regarding the benefit of MT beyond 6 h from symptom onset in large ischemic cores, the short-term benefit of MT in this population after selection by advanced imaging criteria are well known [ 9 13 ]. In contrast, the long-term effects of MT, especially based on advanced imaging criteria, remain poorly described [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among various tools, hypoperfusion severity can be estimated using the hypoperfusion intensity ratio (HIR). Baek et al, studied the association between HIR and clinical outcomes [ 8 ]. They found that the low-HIR group had a more favorable outcome, even with an unfavorable Alberta Stroke Program Early CT score and onset-to-recanalization time.…”
mentioning
confidence: 99%